2018
DOI: 10.1146/annurev-anthro-102116-041320
|View full text |Cite
|
Sign up to set email alerts
|

Looting, the Antiquities Trade, and Competing Valuations of the Past

Abstract: Looting and spoliation of archaeological sites represent a known crisis in many parts of the world, and it is widely acknowledged that despite what we know about the scale of site destruction, the reality is worse. Available evidence suggests that the scale and severity of looting are increasing. Legal and ethical remedies exist but have not proven adequate to reduce the impact of looting and antiquities trafficking. This reflects, in part, inadequate resources and uneven enforcement, and also the pressures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 96 publications
1
8
0
1
Order By: Relevance
“…Regardless of the number of forgeries or fakes, these results suggest what cultures are generally more valued by consumers. The results align with earlier work showing that Western countries dominate sales (Barker, 2018;Bowman, 2008) and that online sales do often have a disproportional representation by few sellers (Huffer and Graham, 2017). Cyprus was shown to be a leading seller; earlier studies have shown Cyprus to have been a major source country for illegal antiquities sold, although it is not clear how significant the country has been relative to other countries (Brodie and Renfrew, 2005).…”
Section: Key Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Regardless of the number of forgeries or fakes, these results suggest what cultures are generally more valued by consumers. The results align with earlier work showing that Western countries dominate sales (Barker, 2018;Bowman, 2008) and that online sales do often have a disproportional representation by few sellers (Huffer and Graham, 2017). Cyprus was shown to be a leading seller; earlier studies have shown Cyprus to have been a major source country for illegal antiquities sold, although it is not clear how significant the country has been relative to other countries (Brodie and Renfrew, 2005).…”
Section: Key Resultssupporting
confidence: 81%
“…The online market is described as a potential grey area of antiquities sales, where objects are often of dubious provenance and are difficult to prove that they derived from legal means. The market of antiquities has been demonstrated to be international, with Western states often dominating sales (Barker, 2018;Bowman, 2008). eBay has emerged as a leading site in the sale of antiquities because it offers an international reach and it makes it easy to sell objects anywhere (Barker, 2018;Fay, 2011).…”
Section: Antiquities Heritage and Online Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the platform is legal but the item sold may not always be legal. The market of antiquities is international, with Western states often seen as key markets for buying and selling antiquities (Barker, 2018;Bowman, 2008). With the nature of Internet sales, and often lack of clear provenance of objects, there is difficulty in knowing whether objects sold on sites such as eBay or others are always legal, while many objects are likely to be fake (Fay, 2011).…”
Section: Online Cultural Heritagementioning
confidence: 99%
“…With the nature of Internet sales, and often lack of clear provenance of objects, there is difficulty in knowing whether objects sold on sites such as eBay or others are always legal, while many objects are likely to be fake (Fay, 2011). Social media, and auction sites such as eBay, do appear to have made the sale of antiquities generally easier and have likely helped to fuel the growth in overall antiquities trading and likely looting of cultural sites (Barker, 2018). In fact, as many sites such as eBay offer lower end antiquities, one argument is they also broaden the market by making it easier to sell lower end antiquities to a wider audience.…”
Section: Online Cultural Heritagementioning
confidence: 99%